Rancang Bangun Geographic Information System (GIS) dengan Algoritma A-star untuk Data Pelanggan dan ODP (Optical Distribution Point) - Miftah Fauziah, Anggita; Elvira Ananda, Fitri; Zulhelman (Politeknik Negeri Jakarta, 2024)
Geographic Information System (GIS) is a technology used to manage spatial data in various applications. This study creates a web-based GIS system design for PT. Aba Telekomunikasi Indonesia, which faces challenges in managing customer data and ODP. The A-star algorithm is applied to find the shortest route between ODP and customers. The system is developed using the CodeIgniter framework, PHP, MySQL, and leaflet.js for map visualization. Testing is carried out by comparing the results of the A-star algorithm with Google maps and using UAT (User Acceptance Test) for user acceptance analysis. The results show an average distance difference of 0.0095 km, meeting a tolerance of 0.2 km, and a user acceptance rate of 84.06%. This study proves that GIS can improve the operational efficiency of small-scale telecommunications companies.